Idea of "federation" in Russian politics and its present implications - Karahan, Abdurrahman Ali (İstanbul Bilgi Üniversitesi, 2021)
ABSTRACT: The trigger of this thesis, which will be presented to the attention of the reader after herein, is the Russian intervention in Syria and the ‘decentralized territorial integrity’ model alleged to be put forward by her afterwards. This situation has created scientific doubt as to whether this model is an ad hoc practice or a commonly propounded proposition in Russian foreign policy. This study is designed to fully understand this and at this point, the federal structure of Russia, which is seen as the usual suspect, is considered as an independent variable. Thus, it was tried to be understood whether the source of the ‘decentralized’ or ‘federalized’ territorial integrity proposal allegedly put forward by Russia in Syria could be the federation model implemented in her own country. At this point, Russia’s unique federation has been examined in depth and it has been understood that Russia’s understanding of territorial integrity is interwoven with its own specific federative structure. In other words, it has been determined that the concepts of ‘asymmetric and matryoshka-like federation’ and ‘territorial integrity’ have almost the same meaning for Russia. Based on this, the question of “does the idea of federation in Russian politics has implications on the solution proposals put forward by Russia in international crises?” was determined as a main research question. Subsequently, it has been proceeded with the hypothesis that this model is a solution proposal frequently offered by Russia and that Russia’s experience of the federation has reflections in the solution proposals suggested by Moscow at the point of solving international crises. Ultimately, it was deemed appropriate to conduct a case study to test this hypothesis, and the Bosnian, Kosovo and Georgia crises, which were the most striking cases of the last quarter century, were considered as cases. The results, at least specific to these cases, does not falsify the hypothesis and indicated that there is a significant relationship between Russia’s federal structure and her solution proposals in the crises in international relations.

ÖZET: İşbu aşamadan sonra okuyucunun dikkatine sunulacak olan bu tezin tetikleyicisi, Rusya’nın Suriye’de yaptığı müdahale ve akabinde ortaya koyduğu iddia edilen ‘âdemi-merkeziyetçi toprak bütünlüğü’ modelidir. Bu durum, bu modelin Rus dış politikasında bir defaya mahsus bir uygulama mı yoksa sıkça rastlanan bir öneri mi olduğu konusunda bilimsel bir şüphe yaratmıştır. Bu çalışma, tam olarak bunu anlamak için tasarlanmış ve bu noktada olağan şüpheli olarak görülen Rusya’nın federal yapısı bağımsız değişken olarak ele alınmıştır. Böylece, Rusya’nın Suriye’de öne sürdüğü iddia edilen ‘âdemi-merkezileşmiş’ veyahut ‘federalleşmiş’ toprak bütünlüğü önerisinin kaynağının kendi ülkesinde uyguladığı federasyon modeli olup olamayacağı anlaşılmaya çalışılmıştır. Bu noktada, Rusya’nın kendine has federasyonu derinlemesine incelenmiş ve Rusya’nın toprak bütünlüğü anlayışının kendine özgü federasyon yapısı ile iç içe geçmiş olduğu anlaşılmıştır. Bir diğer ifadeyle, Rusya için ‘asimetrik ve matruşka benzeri federasyon’ ile ‘toprak bütünlüğü’ kavramlarının neredeyse aynı anlamı taşıdığı tespit edilmiştir. Bundan hareketle, “Rusya siyasetindeki federasyon fikrinin Rusya’nın uluslararası krizlerde öne sürdüğü çözüm önerileri üzerinde yansımaları var mıdır?” sorusu temel araştırma sorusu olarak belirlenmiştir. Takiben, bu modelin Rusya’nın sıkça öne sürdüğü bir çözüm önerisi olduğu ve Rusya’nın federasyon tecrübesinin uluslararası krizlerin çözümü noktasında Moskova’nın öne sürdüğü çözüm önerilerine yansıdığı hipotezi üzerinden hareket edilmiştir. En nihayetinde, bu hipotezin test edilmesi için vaka incelemesi yapılması uygun görülmüş ve son çeyrek asırdaki en çarpıcı vakalar olan Bosna, Kosova ve Gürcistan krizleri birer vaka olarak ele alınmıştır. Ortaya çıkan sonuç, en azından bu vakalar özelinde, hipotezi yanlışlamamış ve Rusya’nın federal yapısı ve Moskova’nın uluslararası ilişkilerde yaşanan krizlerde öne sürdüğü çözüm önerileri arasında anlamlı bir ilişki olduğunu göstermiştir.
Rusya siyasetinde "federasyon" fikri ve mevcut yansımaları
Keywords: Ethno-Federalism; Asymmetry; Hierarchy; Holding-together Federation; Multinationalism; Treaty-based Federation; Territorial Integrity; Etnik-Federalizm; Asimetri; Hiyerarşi; Bir Arada Tutan Federasyon; Çokulusluluk; Antlaşmaya Dayalı Federasyon; Toprak Bütünlüğü